Formulation and Evaluation of Polysaccharide Microparticles for the Controlled Release of Propranolol Hydrochloride - Aneta Stojmenovski; Biljana Gatarić; Sonja Vučen; Maja Railić; Veljko Krstonošić; Radovan Kukobat; Maja Mirjanić; Ranko Škrbić; Anđelka Račić (MDPI AG, 2024)
Propranolol hydrochloride, a non-cardio-selective beta blocker, is used to treat several conditions in children, including hypertension, arrhythmias, hyperthyroidism, hemangiomas, etc. Commercial liquid formulations are available in Europe and the US, but they have disadvantages, such as limited stability, bitter taste, and the need for multiple daily doses due to the drug's short half-life. Considering these limitations, controlled-release solid formulations, such as microparticles, may offer a better solution for pediatric administration. The main objective of this study was to formulate an encapsulation system for propranolol hydrochloride, based on sodium alginate and other polysaccharide polymers, to control and prolong its release. Microparticles were prepared using the ionotropic gelation method, which involves instilling a polymer solution into a solution of gelling ions via the extrusion technique. Physicochemical characterization was conducted by assessing the entrapment efficiency, drug loading, swelling index, microparticle size, rheological properties, and surface tension. In order to improve the characteristics of the tested microparticles, selected formulations were coated with chitosan. Further experimental work included differential scanning calorimetry (DSC), Fourier transform infrared (FTIR) analysis, and SEM imaging. This in vitro release study showed that chitosan-coated microparticles demonstrate favorable properties, suggesting a novel approach to formulating pediatric dosage forms, although further optimization is necessary.